An evaluation of the relationship between violence exposure status and personality characteristics among infertile women - POTUR, DİLEK (TAYLOR & FRANCIS INC, 2019)
In this descriptive study, our aim was to examine the relationship between violence exposure status and personality characteristics among infertile women. The researchers collected data from 315 infertile women at an in vitro fertilization unit of the Woman and Child Disease Training and Research Hospital in Istanbul, Turkey. An introductory information form, the Eysenck Personality Questionnaire Revised-Abbreviated Form (EPQR-A), and the Infertile Women's Exposure to Violence Determination Scale (IWEVDS) were used as data collection tools. When the relationship between the IWEVDS and EPQR-A subdimension scores of the infertile women were examined, a positive relationship was found between the being-forced-into-traditional-practices subdimension of the IWEVDS and the neuroticism subdimension of the EPQR-A. In addition, a weak negative relationship was found between the being-forced-into-traditional-practices subdimension of the IWEVDS and the lying subdimension of the EPQR-A.
Keywords: PREVALENCE